From ferro- to antiferromagnetism via exchange-striction of MnAs/GaAs(001) - Yamaguchi, H; Das, A; Ney, A; Hesjedal, T; Pampuch, C; Schaadt, D; Koch, R (2005)
We investigated the stress evolution in single-crystal MnAs films on GaAs(001) upon applying high external magnetic fields in the α/β phase transition regime (10-40 °C) and beyond. Our stress measurements reveal large field-induced lattice distortions at temperatures, where β-MnAs is present, even well above the phase transition (> 40 °C). A quantitative comparison with the field-induced increase of magnetization reveals that the changes in the lattice dimensions can be fully explained by the (reversible) back-transformation of β-MnAs to α-MnAs. Our direction-dependent experiments identify the structural distortions at the phase transition as a volume magnetostriction effect and - due to the persisting magnetocrystalline anisotropy above 40 °C - strongly support an antiferromagnetic state for β-MnAs. © EDP Sciences.